Kinematic and kinetic comparison between preprofessional pitchers from the Dominican Republic and the United States - Kristen F. Nicholson; Joseph A. Mylott; Tessa C. Hulburt; Tyler J. Hamer; Garrett S. Bullock; Garrett S. Bullock; Garrett S. Bullock (Frontiers Media S.A., 2023)
IntroductionPitching biomechanical efficiency is defined as the association between pitch velocity and arm kinetics. Pitching mechanics inefficiency, an increase in arm kinetics without the resultant increase in pitch velocity, can lead to increased arm strain, increasing arm injury risk. The purpose of this study was to compare arm kinetics, elbow varus torque and shoulder force, in preprofessional United States (US) and Dominican Republic (DR) pitchers. Kinematics that are known to influence elbow varus torque and shoulder force as well as a representative of pitch velocity (hand velocity) were also compared.MethodsA retrospective review was performed on baseball pitchers from the DR and US who participated in biomechanical evaluations conducted by the University biomechanics laboratory personnel. Three-dimensional biomechanical analyses were performed on US (n = 37) and DR (n = 37) baseball pitchers. Potential differences between US and DR pitchers were assessed through analysis of covariance with 95% confidence intervals [95% confidence Interval (CI)].ResultsPreprofessional DR pitchers experienced increased elbow varus torque compared with their US counterparts [DR: 7.5 (1.1); US: 5.9 (1.1) %BWxH; Beta: −2.0 (95% CI: −2.7, −1.2) %BWxH], despite throwing fastballs with slower hand velocity [DR: 3,967.1 (939.4); US: 5,109.1 (613.8) °/s; Beta: 1,129.5 (95% CI: 677.5, 1,581.4) °/s]. DR and US pitchers demonstrated similar shoulder force [DR: 136.8 (23.8); US: 155.0 (25.7); Beta: 0.4 (95% CI: −1.2, 19.7) %BW].DiscussionIncreased elbow varus torque although decreased hand velocity suggests inefficient pitching mechanics among DR pitchers. Inefficient pitching mechanics and increased elbow torque should be considered when developing training programs and pitching plans for professional pitchers from the Dominican Republic.